Evaluating the predictive value of diabetes mellitus diagnosed according to the Chinese guidelines (2020 edition) for cardiovascular events - Zixiang Ye; Yanxiang Gao; Enmin Xie; Yike Li; Ziyu Guo; Peizhao Li; Jingyi Ren; Jingang Zheng (Diabetology & Metabolic Syndrome, 2022)
Abstract Objective Chinese diabetes society has published the new diagnostic criteria for diabetes in China (2020 edition). We aimed to investigate the predictive value of new diabetes-diagnosed criteria for cardiovascular diseases (CVD). Methods A total of 5884 individuals from the China Health and Retirement Longitudinal Study in 2011 and 2018 were enrolled. Baseline characteristics and outcome data were compared. The association between diabetes diagnosed by two criteria and future CVD was identified by Kaplan–Meier curves, Cox regression analyses, and receiver-operating characteristic analyses. Delong’s test was conducted to compare the predictive value for future CVD between diabetes diagnosed by the 2020 edition and diabetes diagnosed by the previous version. Results After multivariate adjustment, both diabetes diagnosed by the 2020 edition and diabetes diagnosed by the previous edition is associated with CVD (HR 1.607, 95% CI 1.221–2.115, P < 0.001; HR 1.244, 95% CI 1.060–1.460, P = 0.007, respectively). The Kaplan–Meier analysis indicated that diabetes patients have more cardiovascular risk (log-rank P<0.001). Moreover, diabetes diagnosed in the 2020 edition illustrated an area under the curve (AUC) of 0.673 for predicting CVD, while diabetes diagnosed in the previous edition showed an AUC of 0.638 (DeLong’s test P<0.01). Conclusion Diabetes diagnosis criteria (2020 edition) in China had better performance in predicting cardiovascular diseases than the previous edition.